Distribution characteristics of temperature, salinity, chlorophyll-a, and sound speed in the Da Nang and Quy Nhon waters - Tu, Tran Anh; Cuong, Le Duc; Cuong, Nguyen Kim; Morimoto, Akihiko (Vietnam Journal of Marine Science and Technology, 2020)
This paper presents some main characteristics of the distributions of temperature, salinity, chlorophyll-a, and sound speed, which were measured in the Da Nang and Quy Nhon waters in July, 2010. The CTD was deployed for measuring profiles of temperature and salinity at stations. The data showed that in the Da Nang water, concentration of chlorophyll-a ranged from 0.07 mg/l to 1.52 mg/l and decreased toward the offshore region. In the Quy Nhon water, concentration of chlorophyll-a varied from 0.05 mg/l to 1.43 mg/l. This concentration was quite small and homogenous from the surface to 28 m depth. The speed of sound in seawater was maximum with value of 1,543.8 m/s in the Da Nang transect while the water layer with the sudden change of sound speed was from 5 m to 10 m deep in nearshore region (from stations D1 to D4), and from 10 to 15 m deep in offshore region (in D5 and D6 stations). Its minimum value in the Da Nang transect is just 1,014 m/s in the bottom. In the Quy Nhon transect, the maximum value of sound speed in seawater was 1,545.2 m/s and the minimum value was 1,515.2 m/s. The nearshore sound velocity reaches its maximum in the surface layer down to 30 m deep and the offshore one is similar down to about 40 m deep, under which, the sound velocity declines steadily.